Nagarī Vaiśālī - Dhūmaketu (Gūrjara Grantharatna Kāryālaya, 2011)
Historical novel based on Āmrapālī, famous beauty woman of Vaishali in Gupta period
Historical novel. - Reprint. Originally published: 1954. - In Gujarati-Schr
Keywords: Gujarati fiction; Āmrapālī fl. 600 B.C